2023
DOI: 10.1101/2023.05.03.539310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kappa Opioid Receptor Antagonism Restores Phosphorylation, Trafficking and Behavior induced by a Disease Associated Dopamine Transporter Variant

Abstract: Aberrant dopamine (DA) signaling is implicated in schizophrenia, bipolar disorder (BPD), autism spectrum disorder (ASD), substance use disorder, and attention-deficit/hyperactivity disorder (ADHD). Treatment of these disorders remains inadequate. We established that the human DA transporter (DAT) coding variant (DAT Val559), identified in individuals with ADHD, ASD, or BPD, exhibits anomalous DA efflux (ADE) that is blocked by therapeutic amphetamines and methylphenidate. As the latter agents have high abuse l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Functional DAT activity on DA-terminals governs extracellular DA dynamics [19]. The fact that DAT kinetic properties and surface expression are dynamically regulated by kinase-mediated phosphorylation and that KOR activation triggers DAT-T53 phosphorylation to stimulate DAT function and surface expression in a heterologous cell culture model [24,25] reveals a potential role of in-vivo DAT-T53 phosphorylation in KOR-mediated DA clearance and KOR-induced aversive behavior and locomotor suppression. However, an investigation of this hypothesis is lacking to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional DAT activity on DA-terminals governs extracellular DA dynamics [19]. The fact that DAT kinetic properties and surface expression are dynamically regulated by kinase-mediated phosphorylation and that KOR activation triggers DAT-T53 phosphorylation to stimulate DAT function and surface expression in a heterologous cell culture model [24,25] reveals a potential role of in-vivo DAT-T53 phosphorylation in KOR-mediated DA clearance and KOR-induced aversive behavior and locomotor suppression. However, an investigation of this hypothesis is lacking to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of DAT phosphorylation in a physiologically relevant model system has yet to be determined. Given the fact that KOR is expressed as a heteroreceptor on DAT expressing DA terminals [11,12], using heterologous expression systems and native rat striatal tissue, we previously demonstrated that KOR agonists upregulate DAT function via ERK1/2 activation and that this regulation requires Thr53 phosphorylation of DAT (pT53-DAT) [24,25]. However, a causative relationship of endogenous pT53-DAT to KOR-mediated DAT upregulation has not yet been investigated, and its contribution to KOR agonist-induced aversion and locomotor suppression is also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic administration of a KOR antagonist restored vesicular DA release and responses to systemic cocaine in DAT Val559 mice (Figure 2). 60 Importantly, this pharmacological intervention normalized multiple behaviours in male and female mice that are affected by DAT Val559 expression 60 …”
Section: Dat Val559 Mice As a Platform For The Evaluation Of Diagnost...mentioning
confidence: 99%
“…Hyperphosphorylation of protein kinase C beta (PKCβ) and calmodulin‐dependent protein kinase II (CamKII) in cells expressing DAT Val559, relative to control cells expressing WT DAT. References: DA K M , DA V max and IC 50 values 29 ; Na + K M (DA efflux) and V max (DA efflux) 31 ; hyperphosphorylation (Ser7, Ser12, Ser13), 32 (Thr53) 36,38,60 ; clustering and lateral mobility 61 ; hyperphosphorylation CamKII 32 ; and PKCβII 27 …”
Section: Dat Val559 In Vitro and In Vivomentioning
confidence: 99%